Предмет: Математика,
автор: Jossirite
log3(54-2x^2+x^2*3^x)=x+3
Ответы
Автор ответа:
0
log3(54-2x^2+x^2*3^x) = x+3 ->
3^(x+3) = 54-2x^2+x^2*3^x -> 27*3^x - 54 = x^2*3^x - 2x^2
-> 27*3^x = x^2*3^x -> x^2 = 27
и второе равенство - 54 = - 2x^2 -> x^2 = 27
x^2 = 27 -> x = 3√3
3^(x+3) = 54-2x^2+x^2*3^x -> 27*3^x - 54 = x^2*3^x - 2x^2
-> 27*3^x = x^2*3^x -> x^2 = 27
и второе равенство - 54 = - 2x^2 -> x^2 = 27
x^2 = 27 -> x = 3√3
Похожие вопросы
Предмет: Русский язык,
автор: kaldarovadinara5
Предмет: Биология,
автор: Аноним
Предмет: История,
автор: nurimankuanysh
Предмет: Математика,
автор: ankaaleksievich
Предмет: Математика,
автор: андрейбелый